ANALYZING ELEMENTARY STUDENTS' MISCONCEPTION PATTERNS IN KEY SCIENCE AND SOCIAL STUDIES (IPAS) TOPICS: IMPLICATIONS FOR INSTRUCTIONAL DESIGN - Yaman Yaman; Ayi Abdurahman; Dewanta Arya Nugraha; Nuris Fattahillah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Persistent misconceptions in foundational science ideas often resist routine instruction, undermine knowledge transfer, and remain hidden when assessments capture answers but not reasoning. Within Indonesia’s integrated Science–Social Studies curriculum (IPAS), such misconceptions can cluster around core topics and shape students’ subsequent learning trajectories. This study maps elementary students’ misconception patterns across five IPAS topics—Force–Motion, Changes of State, Energy, Weather/Water Cycle, and Ecosystems—and translates the findings into design principles for instruction. Using an explanatory sequential mixed-methods design, we collected data from 204 Grade 4–6 students in three public schools via a locally contextualized two-tier diagnostic test and clinical interviews supported by concept cartoons. Instrument quality was adequate (mean Aiken’s V = 0.90; internal reliability per topic = 0.71–0.77; inter-rater reliability ? 0.78). Aggregate responses were distributed as 44.2% scientifically sound, 28.1% partial, and 27.7% strong misconceptions, with a grade-level trend toward improvement. The most persistent hotspots appeared in Ecosystems and Force–Motion. Tiered item sensitivity showed a consistent decrease in misconception rates from Q1 (everyday contexts) to Q4 (diagram/model representations), underscoring the role of multiple representations in bridging non-scientific intuitions. Approximately 9–12% of responses were false positives, highlighting the need to evaluate reasoning in addition to answers. Findings inform operational strategies: eliciting initial ideas with mini two-tier items; orchestrating multiple representations and simple empirical evidence within a 5E sequence with explicit refutation; and embedding metaconceptual reflection with formative assessment attuned to misconception patterns. Limitations include geographic scope and non-causal design. Future work should broaden contexts, test instrument invariance, and evaluate a 5E–refutation package quasi-experimentally.